2007
DOI: 10.1159/000099547
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic HLA-Matched Donor Dendritic Cells Loaded with Patient Leukemic Blasts Preferentially Induce CD4-Positive Leukemia-Reactive Donor Lymphocytes

Abstract: Background: The therapeutic value of donor lymphocyte infusions in patients who relapse with acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (HSCT) is limited by a low efficacy and the risk of graft-versus-host disease. We aimed at generating leukemia-reactive donor T cells for patients with AML. Methods: Peripheral blood mononuclear cells of the donor were stimulated with mature donor dendritic cells, pulsed with irradiated patient leukemic blasts (LB), or directly with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…To mimic CD40L-mediated T-cell help in the lymph node, 23 we also stimulated mature DCs with CD40L-transfected K562 cells. 24 We focused on global transcriptional and on molecular and phenotypic features of the resulting DCs to generate portraits of differential DC maturation. Specifically, we sought to test the hypothesis that a poly(I:C)-based cocktail would induce a stronger T helper (T H ) 1 cytokine milieu characterized by high secretion of IL-12p70 without an impairment in phenotypical maturity, lymph node homing capacity, or immunostimulatory properties through expression of IDO and IL-10.…”
mentioning
confidence: 99%
“…To mimic CD40L-mediated T-cell help in the lymph node, 23 we also stimulated mature DCs with CD40L-transfected K562 cells. 24 We focused on global transcriptional and on molecular and phenotypic features of the resulting DCs to generate portraits of differential DC maturation. Specifically, we sought to test the hypothesis that a poly(I:C)-based cocktail would induce a stronger T helper (T H ) 1 cytokine milieu characterized by high secretion of IL-12p70 without an impairment in phenotypical maturity, lymph node homing capacity, or immunostimulatory properties through expression of IDO and IL-10.…”
mentioning
confidence: 99%
“…Neves and workers 33 reported that they are even better than autologous DCs, especially in cases when the autologous DCs are functionally impaired. DCs generated from HLA‐matched or partially mismatched donors have also shown to induce clinical response 34‐36 . In such circumstances UCB CD34+‐derived DCs will be an attractive source for HLA‐matched or partial mismatched allogeneic DCs.…”
Section: Discussionmentioning
confidence: 99%